Evolution of Spinal Endoscopic Surgery - Kim, Manyoung; Kim, Hyeun-Sung; Oh, Sung Woon; Adsul, Nitin Maruti; Singh, Ravindra; Kashlan, Osama Nezar; Noh, Jung Hoon; Jang, Il Tae; Oh, Seong Hoon (Neurospine, 2019)
Innovations in the development of endoscopic spinal surgery were classified into different generations and reviewed. Future developments and directions for endoscopic spinal surgery were discussed. Surgical therapy for spinal disease has been gradually changing from traditional open surgery to minimally invasive spinal surgery. Recently, endoscopic spinal surgery, which initially was limited to the treatment of soft tissue lesions, has expanded to include other aspects of spinal disease and good clinical results have been reported. As the paradigm of spinal surgery shifts from open surgery to endoscopic surgery, we discussed the evolution of endoscopic spine surgery in our literature review. Through this description, we presented possibilities of future developments and directions in endoscopic spine surgery.